2017
DOI: 10.1111/tbj.12764
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in Interpreting Germline Mutations in BARD1 and ATM in Breast and Ovarian Cancer Patients

Abstract: Next-generation sequencing promotes identification of mutations in non-BRCA1/2 genes in hereditary cancer families. The contribution of mutations in moderate penetrance genes to hereditary cancer risk is not well established. Here, we report a family with early onset breast and fallopian tube cancer that was identified as carrying germline mutations in BARD1 and ATM genes. Loss of heterozygosity studies suggest a causative role of the BARD1 mutation in the development of primary peritoneal cancer, but fail to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Other studies have also suggested distinct and aggressive tumor phenotypes (i.e., TNBCs) associated with BARD1 germline pathogenic variants; empirically, a patient with a nonsense germline variant (c.1921C>T) was found to have multiple bilateral breast cancers (Atchley et al 2008; Sabatier et al 2010; Maxwell et al 2014; Couch et al 2015; Buys et al 2017; Gass et al 2017). However, with BARD1 being a low-penetrance gene, these phenotypes are unlikely caused solely by the respective BARD1 pathogenic variants (DeLeonardis et al 2017). Low- to moderate-penetrance genes have been demonstrated in model-fitting studies, to act multiplicatively in raising cancer risk (Vahteristo et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also suggested distinct and aggressive tumor phenotypes (i.e., TNBCs) associated with BARD1 germline pathogenic variants; empirically, a patient with a nonsense germline variant (c.1921C>T) was found to have multiple bilateral breast cancers (Atchley et al 2008; Sabatier et al 2010; Maxwell et al 2014; Couch et al 2015; Buys et al 2017; Gass et al 2017). However, with BARD1 being a low-penetrance gene, these phenotypes are unlikely caused solely by the respective BARD1 pathogenic variants (DeLeonardis et al 2017). Low- to moderate-penetrance genes have been demonstrated in model-fitting studies, to act multiplicatively in raising cancer risk (Vahteristo et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…We propose that the BRCA1/BARD1 complex acts as a tumor suppressor in estrogen-dependent tissues through H2A ubiquitylation, by suppressing the expression of genes that encode estrogen-metabolizing enzymes. Loss-of-function mutations of BRCA1 and BARD1 lead to increased risk of breast, ovarian, and fallopian tube cancer (11)(12)(13)(14)(15)40), tissues that are exposed to high levels of estrogen and estrogen metabolites over a woman's lifetime. Prophylactic removal of the ovaries and fallopian tubes well before menopause (by about age 40) significantly reduces risk of breast cancer in BRCA1 mutation carriers (41)(42)(43), reflecting the strong influence of estrogen level in tumor formation in these women.…”
Section: Discussionmentioning
confidence: 99%
“…As part of the heterodimer, the BRCA1 RING domain interacts with an E2 enzyme to activate transfer of ubiquitin onto a substrate, but the role of the BARD1 RING domain has remained unknown. Mutations that result in truncation of the BARD1 protein are associated with increased risk of breast and ovarian cancer (11)(12)(13)(14)(15), but the functional and clinical consequences of missense mutations in the BARD1 RING domain have not been characterized. To address these questions, we evaluated three missense mutations in the BARD1 RING domain, newly discovered in families severely affected by breast cancer.…”
mentioning
confidence: 99%
“…7,[17][18][19] More recently, rare coding variants with larger predicted effect sizes were also found to be significantly enriched in the germline of sporadic neuroblastoma patients, including multiple putative loss-of-function (LOF) variants in the BARD1 gene. [20][21][22] Notably, BARD1 coding variants are also enriched in the germline of patients with several other malignancies [23][24][25][26][27][28][29] , suggesting a potential shared mechanism of tumor predisposition across multiple cancers. Large germline sequencing studies in pediatric and adult cancers have successfully described the landscape of cancer-associated germline variation across many malignancies [30][31][32] , but the precise functional implications of these germline variants on tumor development remain largely undefined.…”
Section: Introductionmentioning
confidence: 99%